Optimization of portal steel frame design by computer methods / Mohd. Zaidi Yusoff - Yusoff, Mohd. Zaidi (Faculty of Civil Engineering, 1990)
A computer program in Basic language has been developed for the optimization of steel portal frame design in accordance with the new code of practice - British Standard BS5950 ; Part 1:1985 using IBM – Pc system. The program of steel frame design is also done in Fortran 77 language using mini computer a t I.T.M, Shah Alam. The report includes both manual calculations and use of computer program for veri fication . Together with these,a user's guide on how to use the program has also been included. The program could be further modified to include steel Grade 50 and Grade 55 by altering certain statements in the design program .